THE COMPARISON OF PHONEME PRONUNCIATION PHONOLOGICAL INTERFERENCE OF ق [Q] IN SUNDANESE AND JAVANESE SPEAKERS - Fitria, Siti Aulia Nazarul; Al Farisi, Mohamad Zaka (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
The study analyses the phonological interference of phoneme pronunciation [q] by Sundanese and Javanese speakers compared with Arabic speakers. The researchers used a descriptive comparative qualitative method. The researchers listened, took notes, and documented the voice recordings of male students from the Sundanese and Javanese ethnic groups when reading the Qur'an to collect research data and analyse it using Praat software version 6.2.13. From the results of the recordings, Sundanese-speaking students and Javanese speakers would then be compared with reference speakers, namely Syekh Sa'ad Al-ghamidi, who has the capability of reciting verses from the Qur'an. The research results indicated phonological interference in the phoneme [q] when Sundanese and Javanese male students read the Qur'an. The factor contributing to the occurrence of pronunciation errors in the phoneme [q] was the transfer of SL and JL elements when using AL. Errors occurred due to deviations from the proper language rules. The research is expected to have positive implications, minimizing interference and increasing fluency in reading the Qur'an.